Multivariate analysis of soybean genotypes - Singh, Pallavi Kumari; Shrestha, Jiban; Kushwaha, Ujjawal Kumar Singh (Journal of Agriculture and Natural Resources, 2020)
The experiments were conducted using randomized complete block design with three replications at the research field of Agriculture Botany Division, Khumaltar, Lalitpur, Nepal in 2016 and 2017 to evaluate sixteen soybean genotypes using multivariate analysis. The results showed the significant (p